1989
DOI: 10.1093/jnci/81.14.1061
|View full text |Cite
|
Sign up to set email alerts
|

Human Biologic Response Modification by Interferon in the Absence of Measurable Serum Concentrations: A Comparative Trial of Subcutaneous and Intravenous Interferon-beta serine

Abstract: The effect on a range of biologic responses of interferon-beta serine (IFN-beta ser), administered by either the sc or the iv route, was examined in 16 patients. Despite the absence of IFN in the serum of 13 of 16 patients after sc administration, biologic changes associated with IFN administration occurred. Significant increases in peripheral mononuclear cell surface proteins were evident. Monocyte human leukocyte antigen-DR (HLA-DR) showed a 23% increase in mean fluorescent intensity (P = .04) and a 9% incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Because of IFN-β's well described short half life [43], it is not expected that sufficient levels of injected recombinant IFN-β can be maintained at the tumor site to affect tumor growth before the protein is degraded. However, using MSC to secrete IFN-β in situ would overcome this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Because of IFN-β's well described short half life [43], it is not expected that sufficient levels of injected recombinant IFN-β can be maintained at the tumor site to affect tumor growth before the protein is degraded. However, using MSC to secrete IFN-β in situ would overcome this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Both 2Ј5Ј OAS and neopterin are at least as sensitive as enzyme-linked immunosorbent assay (ELISA) detection of serum interferon. 34 …”
Section: Serum Markers Of Iss Activitymentioning
confidence: 99%
“…NK activity and the percentage of circulating peripheral blood NK cells have not been clearly related to MS [23,30,38]; however, on the assumption that viral infections might play a role at least in the triggering of disease exacerbations [25], therapy with interferon β (IFN-β) has recently been adopted [15]. IFN-β has a boosting effect on NK activity [11].A number of reports have suggested that IFN-Îł [2] and tumour necrosis factor alpha (TNF-Îą) production [6], interleukin 2 (IL-2) or sIL-2R levels [1] are related to the clinical activity of the disease. Both TNF-Îą and IFN-Îł are detected in MS lesions, suggesting a role in inflammatory demyelination [4,33].…”
mentioning
confidence: 99%